An ultrastructural study of the Antarctic Calanoid Copepod Metridia gerlachei Giesbrecht, 1902. Adult female - MARIOTTINI, GIAN LUIGI; ROMANO, PAOLA; CADONI, ANGELA; CARLI, ANNA MARIA; M. Feletti (Idelson, 2000)
Scanning electron microscopy (SEM) can highly contribute to the knowledge of body structures in order to differentiate between different species or between varieties of the same species; this is important in extreme environments, such as in Antarctic waters, where the evolution efforts promoted the development of endemisms. In this work the external anatomy of Metridia gerlachei (Copepoda, Calanoida) adult females, sampled during the Italian Oceanographic Campaign in Antarctica 1987-88, was described by SEM, particularly considering some swimming legs and the genital abdominal joint. The known descriptions have been verified and some morphological details have been better emphasized. In P2 the hook process of the first segment of endopod and a series of spines vaguely indicated, but not defined, in previous descriptions have been clearly evidenced. In P5 the occurrence of three well separated free segments and the location of a marginal seta have been shown. The ultrastructure of the genital segment showed that a clear areola surrounds the genital field.